Molecular Evolution of Plant AAP and LHT Amino Acid Transporters - Tegeder, Mechthild; Ward, John M. (Frontiers in Plant Science, 2012)
Nitrogen is an essential mineral nutrient and it is often transported within living organisms in its reduced form, as amino acids. Transport of amino acids across cellular membranes requires proteins, and here we report the phylogenetic analysis across taxa of two amino acid transporter families, the Amino Acid Permeases (AAPs) and the Lysine-Histidine-like Transporters (LHTs). We found that the two transporter families form two distinct groups in plants supporting the concept that both are essential. AAP transporters seem to be restricted to land plants. They were found in Selaginella moellindorffii and Physcomitrella patens but not in Chlorophyte, Charophyte or Rhodophyte algae. AAPs were strongly represented in vascular plants, consistent with their major function in phloem (vascular tissue) loading of amino acids for sink nitrogen supply. LHTs on the other hand appeared prior to land plants. LHTs were not found in chlorophyte algae Chlamydomonas reinhardtii and Volvox carterii. However, the characean alga Klebsormidium flaccidum encodes KfLHT13 and phylogenetic analysis indicates that it is basal to land plant LHTs. This is consistent with the hypothesis that characean algae are ancestral to land plants. LHTs were also found in both Selaginella moellindorffii and Physcomitrella patens as well as in monocots and eudicots. To date, AAPs and LHTs have mainly been characterized in Arabidopsis (eudicots) and these studies provide clues to the functions of the newly identified homologs.